Urban pollution and changes to materials and building surfaces. Vol.5 - Peter Brimblecombe (London Imperial College Press, 2016)
Pollution damages materials, but it has changed dramatically in the past century, with a reduction in the concentration of corrosive primary pollutants in urban atmospheres. At the same time, architectural styles and types of materials have changed, as we have moved to more organically rich, photo chemically active atmospheres. Contemporary pollutants have a greater potential to degrade organic coatings and polymers, which are of great importance to modern structures.
Keywords: Civil Engineering